STRUCTURE AND FUTURE PROSPECTIVE OF MATRIX METALLOPROTEINASES (Experimental biology, 2021)
Matrix metalloproteinases (MMPs) are group of enzymes responsible for the collagen, and protein degradation in extracellular matrix (ECM). Collagen is the main structural component of connective tissue, and its degradation is an important process in the tissue development, remodeling, and repair. MMP family is divided into 6 groups: collagenases, gelatinases, stromelysins, matrilysins, membrane-type MMPs, and non-classified MMPs. The MMPs, and MMP inhibitors (MMPI) have multiple biological functions in stages of cancer development. MMPs, and MMPI are extensively examined as potential anticancer medications. The need for selective and metabolically stable MMPs and MMP inhibitors determined the effect of their activity on biological systems. In particular, the relationship of MMPs with the immune system has revealed the potential for the use of MMP inhibitors in therapy. As is known, the degree of invasive growth and metastasis of tumor cells are determined by their ability to cleave all ECM structures of the extracellular matrix - only MMPs can do this. It is important to note that ECM affects the behavior of both cancer cells and stromal, endothelial and immune cells in the environment. The fundamentally important role of ECM is dynamism during tissue homeostasis and the ability to regulate the activation of immune cells.